Enhancing competitiveness in an uncertain world - World Bank (Springer, 2015)
In China, growth will gradually moderate, reflecting intensified policy efforts to address financial vulnerabilities and structural constraints, and place the economy on a more sustainable growth path. In the rest of the region, growth will pick up, as exports firm in line with strengthening global activity, and the impact of domestic adjustment in large ASEAN countries eases. Significant uncertainties remain about the sustainability of the global recovery, and global financial conditions are likely to tighten. The short-term priority in several countries is to address the vulnerabilities and inefficiencies created by an extended period of loose financial conditions and fiscal stimulus. In China, the authorities need to strike a balance between containing growing risks from rising leverage and meeting the indicative growth targets.